Body Composition and Cardiometabolic Risk Markers in Children of Women who Took Part in a Randomized Controlled Trial of a Preconceptional Nutritional Intervention in Mumbai, India. Issue 4 (7th January 2022) - Sahariah, Sirazul Ameen; Gandhi, Meera; Chopra, Harsha; Kehoe, Sarah H; Johnson, Matthew J; di Gravio, Chiara; Patkar, Deepak; Sane, Harshad; Coakley, Patsy J; Karkera, Aarti H; Bhat, Dattatray S; Brown, Nick; et al.
ABSTRACT: Background: Maternal nutrition influences fetal development and may permanently alter ("program") offspring body composition and metabolism, thereby influencing later risk of diabetes and cardiovascular (cardiometabolic) disease. The prevalence of cardiometabolic disease is rising rapidly in India. Objectives: To test the hypothesis that supplementing low-income Indian women with micronutrient-rich foods preconceptionally and during pregnancy has a beneficial impact on the children's body composition and cardiometabolic risk marker profiles. Methods: Follow-up of 1255 children aged 5–10 y whose mothers took part in the Mumbai Maternal Nutrition Project [Project "SARAS"; International Standard Randomised Controlled Trial Number (ISRCTN)62811278]. Mothers were randomly assigned to receive a daily micronutrient-rich snack or a control snack of lower micronutrient content, both made from local foods, in addition to normal diet, from before pregnancy until delivery. Children's body composition was assessed using anthropometry and DXA. Their blood pressure, plasma glucose, insulin, and lipid concentrations were measured. Outcomes were compared between allocation groups with and without adjustment for confounding factors. Results: Overall, 15% of children were stunted, 34% were wasted, and 3% were overweight. In the intention-to-treat analysis, there were no differences in body composition or risk markers between children in the intervention and control groups. Among children whose mothers started supplementation ≥3 mo before conception (the "per protocol" sample) the intervention increased adiposity among girls, but not boys. BMI in girls was increased relative to controls by 2% (95% CI: 1, 4; P = 0.01); fat mass index by 10% (95% CI: 3, 18; P = 0.004); and percent fat by 7% (95% CI: 1, 13; P = 0.01) unadjusted, with similar results in adjusted models. Conclusions: Overall, supplementing women with micronutrient-rich foods from before pregnancy until delivery did not alter body composition or cardiometabolic risk markers in the children. Subgroup analyses showed that, if started ≥3 mo before conception, supplementation may increase adiposity among female children.